Mesenchymal Stem Cells Loaded with Gelatin Microcryogels Attenuate Renal Fibrosis. (31st October 2019) - Geng, Xiaodong; Hong, Quan; Chi, Kun; Wang, Shuqiang; Cai, Guangyan; Wu, Di
Abstract : Background . The treatment of chronic kidney diseases (CKDs) by different approaches using mesenchymal stem cells (MSCs) has made great strides. In this study, we aimed to explore the potential mechanism of gelatin microcryogels (GMs) as a cell therapeutic vector to block the progression of CKD. Methods . In vivo, the pedicled omentum valve with MSC-loaded GMs was packed onto 5/6 nephrectomized kidneys derived from rats. The therapeutic effects were evaluated. In vitro, TNF- α, TGF- β, and MSCs were added to the medium of the HK-2 cell culture system, and key genes involved in anti-inflammatory and antifibrosis effects were evaluated by qPCR. Results . After 12 weeks of MSC transplantation, kidney functions, such as serum creatinine, urea nitrogen, and 24-hour urine protein, were significantly improved. The pedicled omentum valve was packed with MSC-loaded GMs onto the 5/6 nephrectomized kidney, and the expressions of collagen IV, α -SMA, and TGF- β were all evaluated by immunohistochemical staining and western blot analysis. MSC-loaded-GMs also showed antifibrotic effects by inducing the upregulation of HO-1, BMP-7, and HGF and the downregulation of MCP-1 at the mRNA level. Four weeks after MSC-loaded GM treatment, we found that the mRNA levels of TNF- α and IL-6 were clearly reduced. MSC-conditional medium (MSC-CM) showed that the TNF- α -induced expression of IL-8 and IL-6 mRNA was reversed; E-cadherin mRNA was upregulated; and the TGF- β -induced expression of collagen IV, α -SMA, and fibronectin (FN) mRNA in HK-2 cells was reduced. Conclusions . We demonstrated that the pedicled omentum valve packed with MSC-loaded GMs had a renal protective effect on the 5/6 nephrectomized kidney by observing the anti-inflammatory and antifibrosis effects.